Preparation method of rose gold sputtering target material

By regulating the composition and structure of Au-Cu binary alloys, and using high-precision process flow to prepare rose gold sputtering targets, solving the problems of poor target quality and process environment pollution in the existing technology, and achieving high-quality coating and environmentally friendly production.

CN119465045APending Publication Date: 2025-02-18GUANGZHOU PANYU POLYTECHNIC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410978732.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The quality of the existing rose gold sputtering targets is poor, resulting in unsatisfactory coating effect, and the process has environmental hazards and high energy consumption and high pollution.

Method used

By comprehensively regulating the composition, structure and performance of Au-Cu binary alloys, vacuum smelting and die-casting processes are used to make ingots, and through precision rolling, vacuum heat treatment, precision milling and other processing technologies, high-quality and structured metallurgical production are prepared. A dense, uniform composition rose gold sputtering target.

Benefits of technology

It achieves high quality of the coating film layer, with a color quality of no less than 18K, and a color better than standard 5N colors. It has good wear resistance and corrosion resistance, and is environmentally friendly in the process, reducing the waste of precious metals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465045A_ABST
    Figure CN119465045A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a rose gold sputtering target material. The preparation method comprises the following steps: designing target material components; smelting and homogenizing treatment; rolling the cast ingot; and the required specification of the rose gold sputtering target material is manufactured according to design requirements. According to the preparation method, according to the special requirements of jewelry product coating on decorativeness, safety, wear resistance and corrosion resistance, based on the Au-Cu binary alloy, the composition, the structure and the performance of the Au-Cu binary alloy are comprehensively regulated and controlled from the aspects of physical performance, chemical performance, mechanical performance, machining performance and the like, the ingot material is manufactured through the vacuum melting and pressure casting technology, and the production cost is reduced. The sputtering target material which is high in metallurgical quality, compact in structure, uniform in component, consistent in orientation and accurate in size is manufactured through machining such as precise rolling, vacuum heat treatment and precise milling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sputtering target materials, and in particular to a method for preparing a rose gold sputtering target material. Background Art

[0002] Rose gold is a gold alloy with a red color. Compared with the gorgeous gold and the low-key platinum, rose gold has become a popular fashion trend in the international jewelry industry today because of its elegant and charming color, gorgeous and elegant, especially in line with the aesthetic taste of the Chinese. Industry insiders give this type of material a romantic name based on its unique color, called rose gold, which represents the eternal theme of mankind---love. Rose gold jewelry, with its unique style and culture, interprets another new world of precious metal jewelry and becomes the "new favorite" of fashion people. Many internationally renowned jewelry and watch brands, such as Titoni, Cartier, Jaeger-LeCoultre, etc., have all launched multiple series of rose gold jewelry and watches without exception, triggering a rose gold fashion trend that is popular all over the world.

[0003] In addition to the use of rose gold in jewelry, the industry also widely uses rose gold as a coating material for craft jewelry. The most widely used is electroplated rose gold. It is an alloy electroplating of Au-Cu binary alloy. The color of the coating is bright and vivid, and the appearance effect is good. However, one of the most prominent problems in the electroplating process of rose gold is environmental hazards. In order to obtain excellent coating effects, the rose gold plating solution system mainly uses potassium cyanide as the main salt and potassium cyanide as the complexing agent. This plating solution has excellent dispersion ability and deep plating ability, and can obtain a delicate and uniform coating. However, since cyanide is a highly toxic chemical, it causes serious damage to both operators and the environment. my country has explicitly restricted the use of cyanide in electroplating production, and the industry is also working hard to develop a gold alloy electroplating solution system with less cyanide and no cyanide. At present, the systems with relatively more applications are sulfite plating solution, citrate plating solution, etc., but there are problems such as poor plating solution stability and unsatisfactory coating effect. In fact, whether it is a clear cyanide plating solution or a cyanide-free or less cyanide plating solution, they all deposit the coating on the surface of jewelry by electroplating. Electroplating is a typical high-energy consumption, high-pollution, and low-efficiency production method, with problems such as small production scale, scattered operation points, backward technology, low industrial level, and many safety hazards.

[0004] In 2015, the Ministry of Industry and Information Technology formulated the "Standardized Conditions for the Electroplating Industry" to promote the industrial structure adjustment and transformation and upgrading of the electroplating industry. In 2017, the Ministry of Environmental Protection issued the national standard "Technical Specifications for the Invention and Issuance of Pollutant Discharge Permits for the Electroplating Industry". The decentralized and extensive electroplating production model of the jewelry industry faces severe challenges and urgently needs to seek new green and environmentally friendly jewelry coating processes.

[0005] Vacuum magnetron sputtering coating belongs to a new generation of surface treatment technology. It ionizes argon gas under certain vacuum conditions. Argon ions are accelerated to bombard the target material under the action of the electric field, sputtering a large number of target atoms, which are deposited on the substrate to form a film. This coating process has the advantages of high sputtering rate, good film uniformity, controllable film thickness, strong bonding with the substrate, and no pollution. It is widely used in aerospace, electronics, optics and other fields. In recent years, magnetron sputtering coating technology has begun to be introduced into the jewelry industry. Sputtering target is the key raw material for magnetron sputtering film preparation, and its quality is one of the key factors determining the performance of the film. However, there are very few precious metal sputtering targets available on the market, and rose gold sputtering targets suitable for jewelry coating decoration are even more scarce.

[0006] Rose gold used to make jewelry on the market is not suitable for direct use as a target material. The main reasons are as follows: First, in terms of color, among K gold jewelry materials, 14K and 18K are the most widely used colors, with standard gold contents of 58.3% and 75% respectively. The rest are copper-based alloy elements, and the color of the alloy is adjusted by the copper content. Due to the unstable chemical properties of copper, poor corrosion resistance and weather resistance, rose gold is prone to dark discoloration during use, which seriously deteriorates the appearance of the product; second, the color of rose gold is not good, the brightness is not enough, and it looks deep, which affects the fashion of the product; third, the existing materials are easy to absorb air and oxidize during smelting and casting, and the crystallization interval is large. Casting is prone to defects such as pores, oxidation inclusions, and loose organization, while the target material requires a high density. Casting defects will deteriorate the coating effect of the target material; fourth, the existing rose gold materials are mostly used for casting and molding, and the cold processing performance is poor, which cannot meet the cold processing requirements of the target material.

[0007] In view of the shortage of rose gold sputtering targets in the current market, some researchers have conducted relevant research and reported some research results. For example, patent CN101358331 discloses a magnetron sputtering rose gold target and its preparation method, the chemical composition of which is: gold 65-78wt%, copper 16-33wt%, yttrium 0.01-4wt%, zinc 1-7wt%, cobalt 0.001-1.2wt%, antimony 0.001-0.2wt%, indium 0.02-5wt%. However, the red color of this sputtering target is too light, the gold color is also low, and it contains harmful heavy metal elements. Patent CN102703751A discloses a low-gold rose gold target for vacuum magnetron sputtering and its preparation method, the composition of the target is 50-60wt.% Au, 30-42wt.% Cu, 1.4-5.0wt.% Zn, 0.5-4.0wt.% Al, 1.0-3.7wt.% In, 0.1-1.3wt.% Co, 0.05-1.5wt.% Y. The gold content of this rose gold target is only 50-60wt.% Au, although the preparation cost is reduced, it is not suitable for surface coating of medium-high color jewelry, and the color of the material is light, the melting and processing performance are not good, and it is easy to have oxidation inclusions, which affects the coating quality. Patent CN104032273A discloses a rose gold target material and its preparation method, the chemical composition of which includes 65-75wt% Au, 15-35wt% Cu, 4-10wt% Ir and 0-2wt% additives. Ir is used to replace Ag to improve the wear resistance and oxidation resistance of the film layer, but a large amount of Ir is very easy to be segregated in the alloy, resulting in uneven color of the film layer, and problems such as mottled spots. Patent CN109182824A discloses a rose gold coating and its preparation process, the composition of the rose gold coating is: 12-20wt% Cu, 5-15wt% Pd, 0.5-0.7wt% Er, 0.1-0.2wt% Nd, and the rest is Au; the high palladium content in the rose gold has a significant bleaching effect on the alloy, affecting the red color of the alloy, and the high content of rare earth elements significantly increases the brittleness of the alloy. Summary of the invention

[0008] In order to overcome the shortcomings of the prior art, the present invention provides a method for preparing a rose gold sputtering target. According to the special requirements of jewelry product coating on decorativeness, safety, wear resistance and corrosion resistance, based on Au-Cu binary alloy, its composition, organization and performance are comprehensively regulated from various aspects such as physical properties, chemical properties, mechanical properties and processing performance, and ingots are made by vacuum melting and pressure casting processes. Through precision rolling, vacuum heat treatment, precision milling and other processing, a sputtering target with high metallurgical quality, dense organization, uniform composition, consistent orientation and precise size is manufactured.

[0009] The present invention is implemented by the following technical solutions:

[0010] A method for preparing a rose gold sputtering target comprises the following preparation steps:

[0011] S1: Target composition design

[0012] The chemical composition of the rose gold sputtering target is made according to the following mass percentages:

[0013] 15-19% Cu, 0.05-0.45% Ru, 0.05-0.2% Ga, the content ratio of Ge to Cu is 1:100-2:100, and the rest is Au, as well as other inevitable impurities;

[0014] The specific technical principles are:

[0015] (1) Gold. It is the basic component element of rose gold, and its content determines the color and performance of the target material. Gold is golden yellow and belongs to warm tones. It is the basis for forming rose gold color through the blending of gold and copper. At the same time, as a decorative protective film layer, in order to ensure that the target material meets the coating color requirements of most jewelry and obtains excellent corrosion resistance, the gold content cannot be too low. Through a large number of experiments, the present invention found that when the gold content is less than 70wt%, the color difference reaches 3.3 after the alloy is immersed in human sweat for 24 hours, which is a color change that is easy to distinguish with the naked eye. As the gold content increases, the corrosion resistance of the alloy in human sweat increases. When the color reaches 18K, the alloy is prone to ordering transformation and leads to brittleness, affecting the processing performance. Further increasing the gold content, the corrosion resistance of the alloy is further improved, and the brittle tendency of the ordering transformation is correspondingly reduced. However, when the gold content exceeds 86wt%, the color of the material is too yellowish and cannot meet the red requirement. The hardness of the material is also low, which is not conducive to the wear resistance of the film layer, and the cost will also increase accordingly. Therefore, the gold content of the present invention is selected to be 80-85wt%.

[0016] (2) Copper. It is a basic alloying element for obtaining red. As the copper content increases, the red-green index a* value of the alloy increases, making the alloy look redder. Therefore, in order to obtain a sufficient red color for the alloy, the copper content cannot be too low. However, copper itself has poor brightness and poor corrosion resistance. It is easy to darken and discolor in the atmosphere, and it is even more prone to corrosion and discoloration when it encounters human sweat. In addition, copper has a strong tendency to absorb air and oxidize during the smelting process, but pores and oxidized inclusions are prone to appear in the casting. The present invention has found through a large number of experiments that for a gold-copper alloy with a gold content of 80wt%, when the copper content is less than 15wt%, the red color of the alloy is relatively light and the decorative effect is not good; and when the copper content is higher than 19wt%, the alloy undergoes an ordered transformation, resulting in a greater tendency for the material to become brittle, and pores and oxidized inclusions are prone to appear during smelting. Therefore, the present invention finally selects a copper content of 15-19wt%.

[0017] (3) Germanium. Germanium added to gold-copper alloys can increase the brightness of the alloy, improve smelting and casting properties, and reduce gas absorption oxidation. The experiments of the present invention show that the content of germanium needs to be determined according to the content of copper. When the ratio of germanium to copper is lower than 1:100, the effect of germanium on improving color and metallurgical quality is not obvious. When the ratio of germanium to copper is higher than 2:100, the red color of the alloy will be reduced, and the ingot will become brittle and the risk of oxidized inclusions will be caused. Therefore, the present invention finally selects a ratio of germanium to copper of 1:100 to 2:100.

[0018] (4) Ruthenium. Ruthenium has a high melting point and good chemical stability. Like gold, it is a precious metal. When added to a gold-copper alloy, it can significantly refine the grains, improve the surface quality of the alloy, and at the same time improve the brightness of the alloy. Experiments of the present invention show that when the ruthenium content is less than 0.05wt%, its effect is not prominent; and when its content exceeds 0.5wt%, defects such as segregation and hard spots are prone to occur, affecting the uniformity of the alloy composition and increasing the difficulty of smelting. Therefore, the present invention ultimately selects a ruthenium content of 0.05 to 0.45wt%.

[0019] (5) Gallium. Gallium can form a dense oxide film on the surface, has excellent antioxidant and corrosion resistance, and has an excellent effect of improving brightness. More importantly, the present invention has found through experiments that a trace amount of gallium in the coating can significantly improve the antibacterial activity of the coating, and achieve the purpose of sterilization and inhibition by interfering with bacterial metabolism. However, when the gallium content is too high, the solidification crystallization interval of the alloy increases, which is not conducive to the densification of the ingot solidification structure. Therefore, the present invention finally selects a gallium content of 0.05 to 0.2wt%.

[0020] In summary, by comprehensively considering the properties of the above materials, according to the special requirements of jewelry product coating for decorativeness, safety, wear resistance and corrosion resistance, based on Au-Cu binary alloy, the composition, organization and performance are comprehensively regulated through multi-element alloying from the aspects of physical properties, chemical properties, mechanical properties, processing performance, etc., and the above material composition is designed.

[0021] S2: Smelting

[0022] (1) Select pure gold, pure copper, pure ruthenium, pure gallium, and pure germanium with a purity of 99.99% as raw materials, and mix the ingredients according to the composition requirements of the materials;

[0023] (2) Formulate a smelting process: Based on the melting point and boiling point of each alloy element, first melt pure copper, pure ruthenium, pure gallium, and pure germanium into a master alloy, and then melt pure gold and the master alloy together to form the required material;

[0024] (3) The specific steps of smelting are:

[0025] ① Preparation of master alloy: Using vacuum suspension furnace smelting process, pure copper, pure ruthenium, and pure germanium are added into the crucible, and pure gallium is placed into the secondary feeding hopper; vacuum is drawn to 4×10 -3 ~5×10 -3 Pa, and then fill it with high-purity argon gas with a purity of 99.999%, so that the gas pressure in the furnace is adjusted to -0.1~-0.05Kpa; start induction heating, control the smelting temperature to 2330~2350℃, after the charge is melted, keep it in this temperature range for 1~2min, so that ruthenium is evenly distributed in the melt, then reduce the temperature to 1200~1250℃, add pure gallium to melt it, keep it in this temperature range for 2~3min, under the action of electromagnetic stirring, the composition and temperature of the molten metal are further uniform; then pour the molten metal into an ingot;

[0026] In this step, a vacuum suspension furnace is used to melt the master alloy, and strong electromagnetic stirring is used to make the composition of the molten metal uniform while avoiding contamination of the crucible to the metal material.

[0027] ②Prepare the required color materials: Mix the pure gold and the intermediate alloy according to the color requirements, use a vacuum suspension furnace for smelting, and evacuate to 4×10 -3 ~5×10 -3 Pa, and then fill in high-purity argon gas with a purity of 99.999%, so that the gas pressure in the furnace is adjusted to -0.1~-0.05Kpa; start induction heating, control the smelting temperature to 1100~1150℃, keep warm for 2~3min, then reduce the temperature of the molten metal to 1020~1050℃, and cast it into ingots;

[0028] S3: Homogenization

[0029] The riser section of the ingot is cut off, and then placed in an inert atmosphere furnace for heating, homogenization treatment, and then quenched in water to obtain an ingot of a single solid solution;

[0030] S4: Ingot rolling

[0031] placing the ingot on a rolling mill for rolling;

[0032] S5: Make the required rose gold sputtering target specifications according to design requirements.

[0033] Further, in step S1, the total content of other inevitable impurities does not exceed 0.1 wt%.

[0034] Furthermore, in step S2, when preparing the intermediate alloy, the particle size of pure ruthenium is controlled between 0.2 and 1 mm, the particle size of pure copper is controlled between 3 and 10 mm, the particle size of pure germanium is controlled between 3 and 10 mm, the particle size of pure gallium is controlled between 3 and 10 mm, and the particle size of pure gold is controlled between 3 and 10 mm.

[0035] In this step, in order to accurately control the color of the target material, it is necessary to first melt pure copper, pure ruthenium, pure gallium, and pure germanium into an intermediate alloy, and then melt pure gold and the intermediate alloy together into the required material. Since the melting point of pure ruthenium is very high, it is a refractory metal, even exceeding the boiling point of gallium. Therefore, in order to reduce the demand for heat capacity during the smelting process of the charge, it is preferred to control the particle size of pure ruthenium between 0.2 and 1 mm, and the particle size of other charges is preferably controlled between 3 and 10 mm. At the same time, when melting the intermediate alloy, first melt pure copper, pure ruthenium, and pure germanium together, and then add pure gallium to them for melting.

[0036] Furthermore, in step S2, when preparing the required color-forming material, 0.5 to 2 seconds after the ingot is poured, the vibration crystallization function and the pressurized solidification function are started, the vibration amplitude is maintained at 1 to 2 mm, the vibration frequency is maintained at 150 to 200 Hz, and high-purity argon gas is filled into the casting chamber at the same time, the gas pressure is 2 to 3 atm, and the pressure is maintained for 180 to 300 seconds.

[0037] In this step, through vibration crystallization, during the solidification process of the molten metal in the ingot mold, the dendrites are broken and broken under the action of vibration, forming a large number of crystal cores, which significantly refines the ingot structure. At the same time, the vibration field also promotes uniform organization and composition, reduces intercrystalline segregation, and effectively reduces gas and impurities. Through pressurized solidification, the shrinkage of the ingot during the solidification process can be compensated in time, which improves the density of the ingot.

[0038] Furthermore, in step S3, the homogenization treatment conditions are: keeping at 760-800°C for 1-2 hours, and cooling to 500-530°C along with the furnace.

[0039] In this step, experiments show that when the solution temperature is too high, the grain size grows abnormally, which is not conducive to the processing performance and surface quality of the target material. When the solution temperature is too low, a single structure cannot be obtained after treatment, which affects the cold processing performance of the ingot. When the water entry temperature is too high, the thermal stress of the ingot is large, which affects the cold processing performance. When the water entry temperature is too low, the ingot undergoes an ordered transformation, resulting in brittleness, which also affects the cold processing performance. To this end, the present invention keeps the ingot at 760-800°C for 1-2h, cools it to 500-530°C with the furnace, and then quenches it in cold water, which not only achieves the purpose of homogenization and solution treatment, but also avoids the problem of thermal stress and ordered transformation affecting the plasticity of the material.

[0040] Further, in step S4, when the ingot is rolled, the single rolling amount is controlled at 5-15% of the ingot thickness. When the total rolling amount reaches 60-70%, intermediate annealing is performed, the billet is heated to 700-730°C, kept warm for 10-20 minutes, cooled to 500-530°C with the furnace, and then quenched in cold water; the rolling operation is repeated until the plate thickness reaches the required range of 6-10 mm, annealing is performed again, and then it is placed in a straightening machine for straightening.

[0041] Furthermore, in step S5, the specific steps are:

[0042] (1) Cutting

[0043] Use laser cutting machine and wire cutting machine to cut the plate to obtain the required target material billet;

[0044] In this step, through experimental comparison, it was found that the target material composed of a combined indirect cooling target made of billet segments and assembled with a copper back plate using a pressure frame has the advantages of less difficulty in production, easier assembly, higher target utilization rate, and easier target repair than the integral welding target material.

[0045] (2) Milling

[0046] The target material blank is milled by CNC machining center and CNC milling machine, so that the surface unevenness of the target material is less than 20μm, the surface roughness is controlled within 0.8-1.6μm, and the straightness of the target material segment bonding surface is controlled within 20μm;

[0047] (3) Target assembly

[0048] The overall structure of the target material includes a target base shield, an insulating pad, a stainless steel water tank, a supporting flange, a cooling water channel, a NdFeB permanent magnet, a copper backing plate, a sealing strip, a rose gold target block, a graphite pad paper, a locking pressure frame and countersunk bolts; it is assembled according to the target material assembly method.

[0049] Furthermore, the target material assembly method adopts a combined target material assembly method, and an adjustment gap of 3 to 5 mm is set between the target material and the pressure frame. Since the target material forms a local etching groove during the sputtering process, the utilization rate of the target material is low. The present invention adopts a combined target material assembly method, and an adjustment gap of 3 to 5 mm is set between the target material and the pressure frame. During use, the target material segment can be easily flipped and offset, so that the etching area will not be concentrated in the same direction and the same position, which effectively improves the utilization rate of the target material, and also reduces the initial thickness of the rose gold target material, reducing the one-time investment of precious metals.

[0050] Furthermore, in the blanking of step S5, the size of the target material billet is controlled to be: length 55-65 mm, width 55-65 mm, thickness 6-10 mm.

[0051] Further, in the target material assembly of step S5, the target material assembly method is as follows: assemble the stainless steel water tank and the target base shield together, and separate the two by an insulating pad; assemble the NdFeB permanent magnets in order on the magnet mounting seat in the stainless steel water tank, with the N pole uniformly facing the target material surface and the S pole as the mounting surface;

[0052] The inner wall of the stainless steel water tank and the NdFeB permanent magnet are dip-coated with nano-coatings to form an anti-corrosion nano-film layer on the surface, which avoids the problem of magnets being easily rusted during the use of the target material and also improves the cooling water quality and cooling effect;

[0053] The cooling water channel is connected and fixed to the stainless steel water tank through a supporting flange, and a copper back plate with a thickness of 5 to 8 mm is set at the opening of the stainless steel water tank;

[0054] Through holes are arranged at equal distances around the copper back plate, corresponding to the bolt holes on the four edges of the opening end of the stainless steel water tank one by one; the copper back plate is locked to the opening end of the stainless steel water tank by countersunk bolts, and a good seal is formed by the embedded sealing rubber ring on the opening end surface;

[0055] A 0.2-0.5mm graphite pad is placed between the copper backing plate and the precious metal target block to tolerate the possible slight deformation of the precious metal target block. Graphite has excellent electrical and thermal conductivity, will not affect the magnetic field distribution of the target material, and can well ensure the good cooling effect of the precious metal target block;

[0056] The locking frame is made of stainless steel and CNC technology. The cross section is bent, and the bending height is 0.5-0.6mm lower than the rose gold target. The inner side of the top of the locking frame is set to a slope with a slope of 15-30°, which not only ensures sufficient rigidity, but also avoids shielding when ions bombard the target surface. The top of the locking frame is provided with bolt holes, which are concentric with the bolt holes of the copper back plate and correspond to the bolt holes on the wall of the stainless steel water tank. The frame is fastened by countersunk bolts, so that the target is firmly locked on the copper back plate.

[0057] Furthermore, the inner dimensions of the locking pressure frame are 3 to 5 mm larger than the outline dimensions of the rose gold target block, so that during use, the target block can be adjusted and shifted to expand the sputtering area of ​​the target material and improve the utilization rate of the precious metal.

[0058] Compared with the prior art, the present invention has the following beneficial effects:

[0059] 1. The preparation method of the rose gold sputtering target of the present invention is based on the special requirements of jewelry product coating for decorativeness, safety, wear resistance and corrosion resistance. Based on Au-Cu binary alloy, its composition, organization and performance are comprehensively regulated from various aspects such as physical properties, chemical properties, mechanical properties and processing properties. Ingots are made by vacuum melting and pressure casting process. Sputtering targets with high metallurgical quality, dense organization, uniform composition, consistent orientation and precise size are made through precision rolling, vacuum heat treatment, precision milling and other processing.

[0060] 2. The design idea of ​​the present invention is as follows: (1) Rose gold used for sputtering targets needs to be based on the gold-copper system, but the colors of these two metals are relatively dark and not bright enough, which cannot meet the bright and fashionable sense of the jewelry film layer; the corrosion resistance is poor and it is easy to become dark and discolored in the atmosphere; it is easy to have coarse grains during casting, the density is not enough, and it is easy to form dispersed oxide inclusions, which affects the surface quality of the target material; it is easy to form Au3Cu ordered phases, resulting in material brittleness and deteriorating its deformation processing performance. Therefore, when developing rose gold, it is necessary to add alloy elements that can improve the microstructure, hardness, corrosion resistance and brightness of the material to the gold-copper system, so that the alloy has good comprehensive performance. (2) After the composition of the target material is determined, its performance depends largely on its preparation process and production quality. Any metallurgical casting defects in the material may affect the quality of the sputtering film layer, resulting in defects such as color difference, pinholes, and sand holes. Therefore, it is necessary to adopt advanced processing and preparation technology to ensure the quality of the film layer. (3) The utilization rate of conventional planar targets. The one-time investment of precious metals is large, and the target structure and assembly method need to be improved to avoid the sputtering and etching areas being concentrated in the same direction and the same position.

[0061] 3. The film layer coated with the target material of the present invention has a color of not less than 18K, which meets the composition requirements of most K gold, and the color is better than the standard 5N color. The brightness value L* is not less than 84, the chromaticity a* value is not less than 10, and the chromaticity b* value is between 20 and 22. After the film layer is immersed in artificial sweat for 24 hours, the color difference does not exceed 3.0, which meets the color requirements of the jewelry film layer. The hardness of the film layer is not less than HV380, and it has excellent wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1 is the microstructure diagram of the target material of Example 1;

[0063] Figure 2 This is a surface morphology image of the target sputtering and etching groove in Example 1;

[0064] Figure 3 It is a visible light reflectance curve diagram of Example 1 and Comparative Example 1;

[0065] Figure 4It is a Tafel curve diagram of Example 1 and Comparative Example 1 in artificial sweat;

[0066] Figure 5 Graph showing impedance values ​​of Example 1 and Comparative Example 1 in artificial sweat;

[0067] Figure 6 This is a microscopic morphology of the target deposited film layer of Comparative Example 1;

[0068] Figure 7 This is a microscopic morphology of the target material deposited film layer of Example 3. DETAILED DESCRIPTION

[0069] The present invention is further described below in conjunction with specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form a new embodiment.

[0070] Example 1

[0071] 1. The target material of this embodiment is rose gold, and its chemical composition is as follows according to mass percentage: 17% Cu, 0.2% Ru, 0.1% Ga, the content ratio of Ge to Cu is 1.5:100, and the rest is Au, and other inevitable impurities.

[0072] 2. Melting

[0073] (1) Select pure gold, pure copper, pure ruthenium, pure gallium, pure germanium, etc. with a purity of 99.99% as raw materials, and mix the ingredients according to the composition requirements of the materials.

[0074] (2) Formulate smelting process.

[0075] The melting points and boiling points of the alloying elements are shown in Table 1.

[0076] Table 1 Melting point and boiling point of each alloy element

[0077] element Au Cu Ru Ge Ga Melting point, °C 1063 1083 2310 937 30 Boiling point, °C 2856 2562 3900 2830 2204

[0078] The particle size of pure ruthenium is controlled between 0.3 and 0.5 mm, and the particle size of other materials is preferably controlled between 5 and 7 mm. At the same time, when melting the master alloy, pure copper, pure ruthenium and pure germanium are first melted together, and then pure gallium is added to them for melting.

[0079] (3) Use a vacuum suspension furnace to melt the master alloy, use strong electromagnetic stirring to make the metal liquid composition uniform, and avoid the crucible from polluting the metal material. Add pure copper, pure ruthenium, and pure germanium into the crucible, and place pure gallium in the secondary feeding hopper. Evacuate to 4.5×10 -3Pa, and then fill it with high-purity argon gas with a purity of 99.999%, so that the gas pressure in the furnace is adjusted to -0.08KPa. Start induction heating, control the melting temperature to 2340℃, and after the charge is melted, keep it in this temperature range for 1.5min to make the ruthenium evenly distributed in the melt, then lower the temperature to 1230℃, add pure gallium to melt it, keep it in temperature for 2.5min, and under the action of electromagnetic stirring, the composition and temperature of the molten metal are further uniform. Then pour the molten metal into an ingot.

[0080] (4) Pure gold and intermediate alloy are mixed according to the color requirements, smelted in a vacuum suspension furnace, and vacuumed to 4.5×10 -3 Pa, and then fill in high-purity argon with a purity of 99.999%, so that the gas pressure in the furnace is adjusted to -0.08KPa. Start induction heating, control the melting temperature to 1130℃, keep warm for 2.5min, and then reduce the temperature of the molten metal to 1030℃ and cast it into an ingot. One second after the ingot is poured, start the vibration crystallization function and the pressurized solidification function, keep the vibration amplitude at 1.5mm, the vibration frequency at 180Hz, and at the same time fill the casting chamber with high-purity argon at a pressure of 2.5atm, and keep the pressure for 240 seconds. Through vibration crystallization, during the solidification process of the molten metal in the ingot mold, the dendrites are broken and broken under the action of vibration, forming a large number of crystal cores, which promotes the obvious refinement of the ingot structure. At the same time, the vibration field also promotes the uniformity of the structure and composition, reduces intercrystalline segregation, and effectively reduces gas and impurities. Through pressurized solidification, the shrinkage of the ingot during the solidification process can be compensated in time, which improves the density of the ingot.

[0081] 3. Homogenization

[0082] After the riser section of the ingot is cut off, the ingot is kept at 780℃ for 1.5h, cooled to 520℃ with the furnace, and then quenched in cold water. This not only achieves the purpose of homogenization and solution treatment, but also avoids the problem of thermal stress and order transformation affecting the plasticity of the material.

[0083] 4. Ingot rolling

[0084] The ingot is placed in a rolling mill for rolling, and the single rolling amount is controlled at 10% of the ingot thickness. When the total rolling amount reaches 65%, intermediate annealing is performed, the billet is heated to 720°C, kept warm for 15 minutes, cooled to 520°C with the furnace, and then quenched in cold water. The rolling operation is repeated until the plate thickness reaches 8mm, annealed again, and then placed in a straightening machine for straightening.

[0085] 5. Cutting

[0086] A laser cutting machine is used to cut the plate to obtain the required target material billet, and the size of the billet is controlled as follows: length 60 mm, width 60 mm, thickness 8 mm.

[0087] 6. Milling

[0088] The target blank is milled by a CNC machining center to ensure that the surface unevenness of the target is less than 15 μm, the surface roughness is controlled within 1.2 μm, and the straightness of the target segment bonding surface is controlled within 15 μm.

[0089] 7. Target assembly

[0090] (1) The overall structure of the target assembly includes the following components: target base shield, insulating pad, stainless steel water tank, support flange, cooling water channel, permanent magnet, copper backing plate, sealing strip, rose gold target block, graphite pad paper, locking pressure frame, countersunk bolts, etc.

[0091] (2) Control of the target material adjustment method: Since the target material forms local etching grooves during the sputtering process, the utilization rate of the target material is low. This application adopts a combined target material assembly method, and a 4mm adjustment gap is set between the target material and the pressure frame. During use, the target material segment can be easily flipped and offset, so that the etching area will not be concentrated in the same direction and the same position, which effectively improves the utilization rate of the target material and reduces the initial thickness of the rose gold target material, reducing the one-time investment of precious metals.

[0092] (3) Target assembly method: Assemble the stainless steel water tank and the shield together, and separate them with an insulating pad; assemble the NdFeB permanent magnets in order on the magnet mounting seat in the water tank, with the N pole uniformly facing the target surface and the S pole as the mounting surface. The inner wall of the water tank and the magnet block are dip-coated with nano-coatings to form an anti-corrosion nano-film layer on the surface, which avoids the problem of easy rust of the magnet during the use of the target material and improves the cooling water quality and cooling effect. The cooling water channel is connected and fixed to the water tank through a supporting flange, and a 6mm thick copper backing plate is set at the opening of the water tank. Through holes are set at equal distances around the copper plate, corresponding to the bolt holes on the four edges of the water tank opening end. The copper backing plate is locked to the water tank opening end by countersunk bolts, and a good seal is formed by the embedded sealing rubber ring on the opening end surface. A 0.3mm graphite pad is set between the copper backing plate and the precious metal target block to tolerate the possible slight deformation of the precious metal target block. Graphite has excellent electrical and thermal conductivity, will not affect the magnetic field distribution of the target material, and can well ensure the good cooling effect of the precious metal target block. The press frame is made of stainless steel and CNC technology, with a bent cross section, and the bending height is 0.55mm lower than the precious metal target block. The inner side of the top of the press frame is set to a slope with a slope of 20°, which not only ensures sufficient rigidity, but also avoids the shielding effect when the ions bombard the target surface. Bolt holes are set on the top of the press frame, which are concentric with the bolt holes of the copper back plate and correspond to the bolt holes on the wall of the stainless steel water tank. The press frame is tightened by countersunk bolts, so that the target material is firmly locked on the copper back plate. The internal dimensions of the locking press frame are 4mm larger than the outline dimensions of the precious metal target block, so that the target block can be adjusted and shifted during use, the sputtering area of ​​the target material can be expanded, and the utilization rate of precious metals can be improved.

[0093] Example 2

[0094] 1. The target material of this embodiment is rose gold, and its chemical composition is as follows according to mass percentage: 15% Cu, 0.45% Ru, 0.2% Ga, the content ratio of Ge to Cu is 2:100, and the rest is Au, as well as other inevitable impurities.

[0095] 2. Melting

[0096] (1) Select pure gold, pure copper, pure ruthenium, pure gallium, pure germanium, etc. with a purity of 99.99% as raw materials, and mix the ingredients according to the composition requirements of the materials.

[0097] (2) The particle size of pure ruthenium is controlled between 0.7 and 1.0 mm, and the particle size of other materials is preferably controlled between 3 and 5 mm. At the same time, when melting the master alloy, firstly melt the pure copper, pure ruthenium and pure germanium together, and then add the pure gallium to them for melting.

[0098] (3) Use a vacuum suspension furnace to melt the master alloy, use strong electromagnetic stirring to make the metal liquid composition uniform, and avoid the crucible from polluting the metal material. Add pure copper, pure ruthenium, and pure germanium into the crucible, and place pure gallium in the secondary feeding hopper. Evacuate to 5×10 -3 Pa, and then fill it with high-purity argon gas with a purity of 99.999%, so that the gas pressure in the furnace is adjusted to -0.05KPa. Start induction heating, control the melting temperature to 2350℃, and after the charge is melted, keep it in this temperature range for 2 minutes to make the ruthenium evenly distributed in the melt, then lower the temperature to 1250℃, add pure gallium to melt it, keep it in temperature for 3 minutes, and under the action of electromagnetic stirring, the composition and temperature of the molten metal are further uniform. Then pour the molten metal into an ingot.

[0099] (4) Pure gold and intermediate alloy are mixed according to the color requirements, and a vacuum suspension furnace is preferably used for smelting, and the vacuum is evacuated to 5×10 -3 Pa, and then fill in high-purity argon with a purity of 99.999%, so that the gas pressure in the furnace is adjusted to -0.05KPa. Start induction heating, control the melting temperature to 1150℃, keep warm for 3min, then reduce the temperature of the molten metal to 1050℃, and cast it into an ingot. After the ingot is poured for 0.5 seconds, start the vibration crystallization function and pressurized solidification function, keep the vibration amplitude at 2mm, the vibration frequency at 150Hz, and at the same time fill the casting chamber with high-purity argon at a pressure of 3atm, and keep the pressure for 300 seconds. Through vibration crystallization, during the solidification process of the molten metal in the ingot mold, the dendrites are broken and broken under the action of vibration, forming a large number of crystal cores, which makes the ingot structure significantly refined. At the same time, the vibration field also promotes the uniformity of structure and composition, reduces intercrystalline segregation, and effectively reduces gas and impurities. Through pressurized solidification, the shrinkage of the ingot during the solidification process can be compensated in time, which improves the density of the ingot.

[0100] 3. Homogenization

[0101] After the riser section of the ingot is cut off, the ingot is kept at 800℃ for 1h, cooled to 530℃ with the furnace, and then quenched in cold water.

[0102] 4. Ingot rolling

[0103] The ingot is placed in a rolling mill for rolling, and the single rolling amount is controlled at 5% of the ingot thickness. When the total rolling amount reaches 60%, intermediate annealing is performed, the billet is heated to 730°C, kept warm for 10 minutes, cooled to 530°C with the furnace, and then quenched in cold water. The rolling operation is repeated until the plate thickness reaches the required range of 10mm, annealing is performed again, and then it is placed in a straightening machine for straightening.

[0104] 5. Cutting

[0105] The plate is cut by a wire cutting machine to obtain the required target material billet, and the size of the billet is controlled as follows: length 65mm, width 65mm, thickness 6mm.

[0106] 6. Milling

[0107] The target blank is milled by a CNC milling machine to ensure that the surface unevenness of the target is less than 18 μm, the surface roughness is controlled at 1.6 μm, and the straightness of the target segment bonding surface is controlled within 18 μm.

[0108] 7. Target assembly

[0109] (1) The overall structure of the target assembly includes the following components: target base shield, insulating pad, stainless steel water tank, support flange, cooling water channel, permanent magnet, copper backing plate, sealing strip, rose gold target block, graphite pad paper, locking pressure frame, countersunk bolts, etc.

[0110] (2) Control of target adjustment method: A combined target assembly method is adopted, and a 5mm adjustment gap is set between the target and the pressure frame. During use, the target segment can be easily flipped and offset so that the etching area will not be concentrated in the same direction and the same position, which effectively improves the utilization rate of the target and reduces the initial thickness of the rose gold target, reducing the one-time investment of precious metals.

[0111] (3) Target assembly method: Assemble the stainless steel water tank and the shield together, and separate them with an insulating pad; assemble the NdFeB permanent magnets in order on the magnet mounting seat in the water tank, with the N pole uniformly facing the target surface and the S pole as the mounting surface. The inner wall of the water tank and the magnet block are dip-coated with nano-coating to form an anti-corrosion nano-film layer on the surface, which avoids the problem of easy rust of the magnet during the use of the target material and improves the cooling water quality and cooling effect. The cooling water channel is connected and fixed to the water tank through a supporting flange, and a copper backing plate with a thickness of 8 mm is set at the opening of the water tank. Through holes are set at equal distances around the copper plate, corresponding to the bolt holes on the four edges of the water tank opening end. The copper backing plate is locked to the water tank opening end by countersunk bolts, and a good seal is formed with the help of the embedded sealing rubber ring on the opening end face. A 0.5 mm graphite pad is set between the copper backing plate and the precious metal target block to tolerate the slight deformation that may occur in the precious metal target block. Graphite has excellent electrical and thermal conductivity, will not affect the magnetic field distribution of the target material, and can well ensure the good cooling effect of the precious metal target block. The press frame is made of stainless steel and CNC technology, with a bent cross section, and the bending height is 0.6mm lower than the precious metal target block. The inner side of the top of the press frame is set to a slope with a slope of 15°, which not only ensures sufficient rigidity, but also avoids the shielding effect when the ions bombard the target surface. Bolt holes are set on the top of the press frame, which are concentric with the bolt holes of the copper back plate and correspond to the bolt holes on the wall of the stainless steel water tank. The press frame is tightened by countersunk bolts, so that the target material is firmly locked on the copper back plate. The internal dimensions of the locking press frame are 5mm larger than the outline dimensions of the precious metal target block, so that the target block can be adjusted and displaced during use, the sputtering area of ​​the target material can be expanded, and the utilization rate of precious metals can be improved.

[0112] Example 3

[0113] 1. The target material of this embodiment is rose gold, and its chemical composition is as follows according to mass percentage: 19% Cu, 0.05% Ru, 0.05% Ga, the content ratio of Ge to Cu is 1:100, and the rest is Au, and other inevitable impurities.

[0114] 2. Melting

[0115] (1) Select pure gold, pure copper, pure ruthenium, pure gallium, pure germanium, etc. with a purity of 99.99% as raw materials, and mix the ingredients according to the composition requirements of the materials.

[0116] (2) Formulate a smelting process. The particle size of pure ruthenium is controlled between 0.2 and 0.4 mm, and the particle size of other materials is preferably controlled between 7 and 10 mm. At the same time, when melting the intermediate alloy, first melt pure copper, pure ruthenium, and pure germanium together, and then add pure gallium to them for melting.

[0117] (3) Use a vacuum suspension furnace to melt the master alloy, use strong electromagnetic stirring to make the metal liquid composition uniform, and avoid the crucible from contaminating the metal material. Add pure copper, pure ruthenium, and pure germanium into the crucible, and place pure gallium in the secondary feeding hopper. Evacuate to 4×10 -3 Pa, and then fill it with high-purity argon gas with a purity of 99.999%, so that the gas pressure in the furnace is adjusted to -0.05KPa. Start induction heating, control the melting temperature to 2330℃, and after the charge is melted, keep it in this temperature range for 1min to make the ruthenium evenly distributed in the melt, then lower the temperature to 1200℃, add pure gallium to melt it, keep it in temperature for 2min, and under the action of electromagnetic stirring, the composition and temperature of the molten metal are further uniform. Then pour the molten metal into an ingot.

[0118] (4) Pure gold and intermediate alloy are mixed according to the color requirements, and a vacuum suspension furnace is preferably used for smelting, and the vacuum is evacuated to 4×10 -3 Pa, and then fill in high-purity argon with a purity of 99.999%, so that the gas pressure in the furnace is adjusted to -0.1KPa. Start induction heating, control the melting temperature to 1200℃, keep warm for 2min, and then pour the molten metal into ingots. After 2 seconds of ingot pouring, start the vibration crystallization function and pressurized solidification function, keep the vibration amplitude at 1mm, the vibration frequency at 200Hz, and at the same time fill the casting chamber with high-purity argon at a pressure of 2atm, and keep the pressure for 180 seconds. Through vibration crystallization, during the solidification process of the molten metal in the ingot mold, the dendrites are broken and broken under the action of vibration, forming a large number of crystal cores, which promotes the obvious refinement of the ingot structure. At the same time, the vibration field also promotes the uniformity of structure and composition, reduces intercrystalline segregation, and effectively reduces gas and impurities. Through pressurized solidification, the shrinkage of the ingot during the solidification process can be compensated in time, which improves the density of the ingot.

[0119] 3. Homogenization

[0120] The riser section of the ingot is cut off, and then placed in an inert atmosphere furnace for heating for homogenization treatment, and then quenched into water to obtain a single solid solution. Experiments show that when the solid solution temperature is too high, the grain size grows abnormally, which is not conducive to the processing performance and surface quality of the target material. When the solid solution temperature is too low, a single structure cannot be obtained after treatment, affecting the cold working performance of the ingot. When the water entry temperature is too high, the thermal stress of the ingot is large, which affects the cold working performance. When the water entry temperature is too low, the ingot undergoes an ordered transformation, resulting in brittleness, which also affects the cold working performance. For this reason, the present application keeps the ingot at 760°C for 2h, cools it to 500°C with the furnace, and then quenches it into cold water, which not only achieves the purpose of homogenization and solid solution treatment, but also avoids the problem of thermal stress and ordered transformation affecting the plasticity of the material.

[0121] 4. Ingot rolling

[0122] The ingots are placed in the rough rolling mill, the intermediate rolling mill, and the finishing rolling mill for rolling. The single rolling amount is controlled at 15% of the ingot thickness. When the total rolling amount reaches 70%, intermediate annealing is performed, the billet is heated to 700℃, kept warm for 20 minutes, cooled to 500℃ with the furnace, and then quenched in cold water. The rolling operation is repeated until the plate thickness reaches the required 6mm range, annealing is performed again, and then it is placed in the straightening machine for straightening.

[0123] 5. Cutting

[0124] A laser cutting machine is used to cut the plate to obtain the required target material billet, and the size of the billet is controlled as follows: length 55 mm, width 55 mm, thickness 6 mm.

[0125] 6. Milling

[0126] The target blank is milled by a CNC machining center to ensure that the surface unevenness of the target is less than 15 μm, the surface roughness is controlled at 0.8 μm, and the straightness of the target segment bonding surface is controlled within 15 μm.

[0127] 7. Target assembly

[0128] (1) The overall structure of the target assembly includes the following components: target base shield, insulating pad, stainless steel water tank, support flange, cooling water channel, permanent magnet, copper backing plate, sealing strip, rose gold target block, graphite pad paper, locking pressure frame, countersunk bolts, etc.

[0129] (2) Control of target adjustment method: A combined target assembly method is adopted, and a 3mm adjustment gap is set between the target and the pressure frame. During use, the target segment can be easily flipped and offset so that the etching area will not be concentrated in the same direction and the same position, which effectively improves the utilization rate of the target and reduces the initial thickness of the rose gold target, reducing the one-time investment of precious metals.

[0130] (3) Target assembly method: Assemble the stainless steel water tank and the shield together, and separate them with an insulating pad; assemble the NdFeB permanent magnets in order on the magnet mounting seat in the water tank, with the N pole uniformly facing the target surface and the S pole as the mounting surface. The inner wall of the water tank and the magnet block are dip-coated with nano-coatings to form an anti-corrosion nano-film layer on the surface, which avoids the problem of easy rust of the magnet during the use of the target material and improves the cooling water quality and cooling effect. The cooling water channel is connected and fixed to the water tank through a supporting flange, and a 5mm thick copper backing plate is set at the opening of the water tank. Through holes are set at equal distances around the copper plate, corresponding to the bolt holes on the four edges of the water tank opening end. The copper backing plate is locked to the water tank opening end by countersunk bolts, and a good seal is formed with the help of the embedded sealing rubber ring on the opening end face. A 0.2mm graphite pad is set between the copper backing plate and the precious metal target block to tolerate the slight deformation that may occur in the precious metal target block. Graphite has excellent electrical and thermal conductivity, will not affect the magnetic field distribution of the target material, and can well ensure the good cooling effect of the precious metal target block. The press frame is made of stainless steel and CNC technology, with a bent cross section, and the bending height is 0.5mm lower than the precious metal target block. The inner side of the top of the press frame is set to a slope with a slope of 30°, which not only ensures sufficient rigidity, but also avoids the shielding effect when the ions bombard the target surface. Bolt holes are set on the top of the press frame, which are concentric with the bolt holes of the copper back plate and correspond to the bolt holes on the wall of the stainless steel water tank. The press frame is tightened by countersunk bolts, so that the target material is firmly locked on the copper back plate. The internal dimensions of the locking press frame are 3mm larger than the outline dimensions of the precious metal target block, so that the target block can be adjusted and displaced during use, the sputtering area of ​​the target material can be expanded, and the utilization rate of precious metals can be improved.

[0131] Comparative Example 1

[0132] Comparative Example 1 is a sputtering target made of Au85Cu15.

[0133] Performance Testing

[0134] 1. Microstructure

[0135] The rose gold target material prepared in Example 1 has the contents of H, O, N and other integral elements in its chemical composition as shown in Table 1. The microstructure of the rolled state is as shown in Table 1. Figure 1 The target material has a dense structure, fine grains, no pinholes and oxide inclusions, which is conducive to obtaining uniform sputtering and obtaining a high-quality sputtering film. After sputtering, the surface morphology of the etched groove is as follows Figure 2 As shown, the groove surface structure is dense, the grains are uniform, and there is no splashing problem caused by pores, oxide inclusions, etc. during the sputtering process.

[0136] 2. Target material and film color

[0137] The sputtering targets were prepared by using Example 1 and Au85Cu15 Comparative Example 1. After the targets were polished, the reflectivity of the targets to visible light was compared. Figure 3 As shown, the reflectivity of Example 1 is higher than that of Comparative Example 1 in the wavelength range of 360 to 510 nm and the wavelength range of 610 to 740 nm.

[0138] Rose gold films were deposited on a stainless steel substrate using the targets of Examples 1-3 and Comparative Example 1. The color index comparison of the films is shown in Table 2. The brightness of Examples 1-3 is significantly higher than that of Comparative Example 1, and they have better red index, so the color is more fashionable.

[0139] Table 2 Initial colors of the targets of Examples 1-3 and Comparative Example 1

[0140] Material L* a* b* Example 1 85.62 8.88 17.54 Example 2 85.88 7.98 20.00 Example 3 85.34 9.62 19.13 Comparative Example 1 83.53 8.52 20.27

[0141] 3. Corrosion resistance of target material and film layer

[0142] The polarization curve and impedance of the target material in artificial sweat were detected by an electrochemical workstation. The results were as follows: Figure 4 and Figure 5 As shown, the self-corrosion potential of Example 1 is higher than that of Comparative Example 1, the corrosion current is lower than that of Comparative Example 1, and the impedance value is also higher than that of Comparative Example 1. Therefore, the corrosion resistance of Example 1 in artificial sweat is better than that of Comparative Example 1.

[0143] 4. Hardness of target coating layer

[0144] Sputtering targets were prepared using Examples 1-3 and Au85Cu15 Comparative Example 1, respectively, and a rose gold film layer was deposited on a white copper substrate. The comparison of the indentation modulus and hardness of the film layer is shown in Table 3. The film layer plated in Examples 1-3 has a higher hardness than the film layer plated in Comparative Example 1, and therefore has better wear resistance.

[0145] Table 3 Modulus and hardness of target deposited films of Examples 1-3 and Comparative Example 1

[0146]

[0147] 5. Film microstructure

[0148] The surface microstructures of the plated films of Example 3 and Comparative Example 1 were observed under high magnification using a scanning electron microscope. Figure 6 and Figure 7 As shown, the grain size of the plated film layer in Example 3 is obviously smaller than that in the coating layer, which is more beneficial to the physical and chemical properties of the film layer.

[0149] 6. Target utilization

[0150] Comparative Example 1 was used to make a target material according to the prior art, and Example 1 was used to make a target material using the technology of the present invention. Both were coated under the same process conditions. Test results showed that the target material utilization rate of Comparative Example 1 was about 27%, and the target material utilization rate of Example 1 reached 41%, an increase of 52%.

[0151] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A method for preparing a rose gold sputtering target, characterized in that: The method comprises the following preparation steps: S1: Target composition design The chemical composition of the rose gold sputtering target is made according to the following mass percentages: 15-19% Cu, 0.05-0.45% Ru, 0.05-0.2% Ga, the content ratio of Ge to Cu is 1:100-2:100, and the rest is Au, as well as other inevitable impurities; S2: Smelting (1) Select pure gold, pure copper, pure ruthenium, pure gallium, and pure germanium with a purity of 99.99% as raw materials, and mix the ingredients according to the composition requirements of the materials; (2) Formulate a smelting process: Based on the melting point and boiling point of each alloy element, first melt pure copper, pure ruthenium, pure gallium, and pure germanium into an intermediate alloy, and then melt pure gold and the intermediate alloy together to form the required material; (3) The specific steps of smelting are: ① Preparation of master alloy: Using vacuum suspension furnace smelting process, pure copper, pure ruthenium and pure germanium are added into the crucible, and pure gallium is placed into the secondary feeding hopper; Vacuum to 4×10 -3 ~5×10 -3 Pa, and then fill it with high-purity argon gas with a purity of 99.999%, so that the gas pressure in the furnace is adjusted to -0.1~-0.05Kpa; start induction heating, control the smelting temperature to 2330~2350℃, after the charge is melted, keep it in this temperature range for 1~2min, so that ruthenium is evenly distributed in the melt, then reduce the temperature to 1200~1250℃, add pure gallium to melt it, keep it in this temperature range for 2~3min, under the action of electromagnetic stirring, the composition and temperature of the molten metal are further uniform; then pour the molten metal into an ingot; ②Prepare the required color materials: Mix the pure gold and the intermediate alloy according to the color requirements, use a vacuum suspension furnace for smelting, and evacuate to 4×10 -3 ~5×10 -3 Pa, and then fill in high-purity argon gas with a purity of 99.999%, so that the gas pressure in the furnace is adjusted to -0.1~-0.05Kpa; start induction heating, control the smelting temperature to 1100~1150℃, keep warm for 2~3min, then reduce the temperature of the molten metal to 1020~1050℃, and cast it into ingots; S3: Homogenization The riser section of the ingot is cut off, and then placed in an inert atmosphere furnace for heating, homogenization treatment, and then quenched in water to obtain an ingot of a single solid solution; S4: Ingot rolling placing the ingot on a rolling mill for rolling; S5: Make the required rose gold sputtering target specifications according to design requirements.

2. The method for preparing a rose gold sputtering target according to claim 1, characterized in that: In step S2, when preparing the intermediate alloy, the particle size of pure ruthenium is controlled between 0.2 and 1 mm, the particle size of pure copper is controlled between 3 and 10 mm, the particle size of pure germanium is controlled between 3 and 10 mm, the particle size of pure gallium is controlled between 3 and 10 mm, and the particle size of pure gold is controlled between 3 and 10 mm.

3. The method for preparing a rose gold sputtering target according to claim 1, characterized in that: In step S2, when preparing the required color-forming material, 0.5 to 2 seconds after the ingot is poured, the vibration crystallization function and the pressurized solidification function are started, the vibration amplitude is maintained at 1 to 2 mm, the vibration frequency is maintained at 150 to 200 Hz, and high-purity argon gas is filled into the casting chamber at a pressure of 2 to 3 atm for 180 to 300 seconds.

4. The method for preparing a rose gold sputtering target according to claim 1, characterized in that: In step S3, the homogenization treatment conditions are: keeping at 760-800°C for 1-2 hours, and cooling to 500-530°C along with the furnace.

5. The method for preparing a rose gold sputtering target according to claim 1, characterized in that: In step S4, when the ingot is rolled, the single rolling amount is controlled at 5-15% of the ingot thickness. When the total rolling amount reaches 60-70%, intermediate annealing is performed, the billet is heated to 700-730°C, kept warm for 10-20 minutes, cooled to 500-530°C with the furnace, and then quenched in cold water; the rolling operation is repeated until the plate thickness reaches the required range of 6-10 mm, annealing is performed again, and then it is placed in a straightening machine for straightening.

6. The method for preparing a rose gold sputtering target according to claim 1, characterized in that: In step S5, the specific steps are: (1) Cutting Use laser cutting machine and wire cutting machine to cut the plate to obtain the required target material billet; (2) Milling The target material blank is milled by CNC machining center and CNC milling machine, so that the surface unevenness of the target material is less than 20μm, the surface roughness is controlled within 0.8-1.6μm, and the straightness of the target material segment bonding surface is controlled within 20μm; (3) Target assembly The overall structure of the target material includes a target base shield, an insulating pad, a stainless steel water tank, a supporting flange, a cooling water channel, a NdFeB permanent magnet, a copper backing plate, a sealing strip, a rose gold target block, a graphite pad paper, a locking pressure frame and countersunk bolts; it is assembled according to the target material assembly method.

7. The method for preparing a rose gold sputtering target according to claim 6, characterized in that: In the blanking of step S5, the size of the target billet is controlled to be: length 55-65 mm, width 55-65 mm, thickness 6-10 mm.

8. The method for preparing a rose gold sputtering target according to claim 6, characterized in that: In the target material assembly of step S5, the target material assembly method is as follows: assemble the stainless steel water tank and the target base shield together, and separate the two by an insulating pad; assemble the NdFeB permanent magnets in order on the magnet mounting seat in the stainless steel water tank, with the N pole uniformly facing the target material surface and the S pole as the mounting surface; The inner wall of the stainless steel water tank and the NdFeB permanent magnet are dip-coated with nano-coatings to form an anti-corrosion nano-film layer on the surface; The cooling water channel is connected and fixed to the stainless steel water tank through a supporting flange, and a copper back plate with a thickness of 5 to 8 mm is set at the opening of the stainless steel water tank; Through holes are arranged at equal distances around the copper back plate, corresponding to the bolt holes on the four edges of the open end of the stainless steel water tank one by one; the copper back plate is locked to the open end of the stainless steel water tank by countersunk bolts; A 0.2-0.5 mm graphite pad is placed between the copper backing plate and the noble metal target block; The locking frame is made of stainless steel and CNC technology. The cross-section is bent, and the bending height is 0.5 to 0.6 mm lower than the rose gold target block. The inner side of the top of the locking frame is set to a slope with a slope of 15 to 30 degrees. A bolt hole is set on the top of the locking frame, which is concentric with the bolt hole of the copper back plate and corresponds to the bolt hole on the wall of the stainless steel water tank. The frame is fastened by countersunk bolts.

9. The method for preparing a rose gold sputtering target according to claim 8, characterized in that: The inner dimensions of the locking pressure frame are 3 to 5 mm larger than the outline dimensions of the rose gold target block.

Citation Information

Patent Citations

  • Low-gold-content rose gold target material for vacuum magnetron sputtering and preparation method thereof

    CN102703751A

  • Fastness rose gold target and preparation method thereof

    CN104032273A

  • Oxidation-resistant rose gold plating and preparation process thereof

    CN109182824A